Clinical assessment of non carious cervical lesion using swept‐source optical coherence tomography. Issue 10 (11th December 2014) - Wada, Ikumi; Shimada, Yasushi; Ikeda, Masaomi; Sadr, Alireza; Nakashima, Syozi; Tagami, Junji; Sumi, Yasunori
<x xml:space="preserve">Abstract</x> Non‐carious cervical lesions (NCCLs) involve various forms of tooth loss with different etiologies. This study aimed to utilize swept‐source optical coherence tomography (SS‐OCT) at 1300 nm wavelength range in vitro and in vivo to evaluate and clarify the mechanism of NCCLs. In the in vitro phase, a dentin attenuation coefficient (μt) derived from the SS‐OCT signal at NCCL was compared with mineral loss obtained from transverse microradiography (TMR) to determine a μt threshold to discriminate demineralization of cervical dentin in vivo. In the clinical study, 242 buccal surfaces were investigated in 35 subjects. Presence and dimensions of NCCLs, cervical cracking and the degree of demineralization at the exposed cervical dentin were determined using SS‐OCT. Dentin demineralization was observed in 69% of NCCLs. SS‐OCT results confirm that dentin mineral loss and occlusal attrition were associated with larger NCCLs, and can be considered as an etiological factor in formation and progress of these lesions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> (A) We determined the attenuation coeffcient (μt) threshold of SS‐OCT signal for the detection of demineralization (1.21) from in vitro study. DEM: demineralized dentin, sound: sound dentin. (B) Using the μt threshold, we observed NCCLs in vivo to detect the demineralization in cervical dentin. SS‐OCT scanning was performed along the red line. (C) SS‐OCT image obtained along the red line in B. In SS‐OCT, brightness of dentin beneath the NCCL was increased (arrow) compared with intact zone. The cervical dentin was slightly demineralized (μt: 1.25). e: enamel, d: dentin, g: gingiva. </boxed-text>